EFFECT OF DIFFERENT CATALYST TOWARDS THE EPOXIDATION OF NEEM OIL VIA IN SITU PERACIDS MECHANISM - Rasib, I. M.; Azmi, I. S.; Jalil, M. J.; Rahim, N. R. (Journal of Engineering and Technology (JET), 2025)
Currently, concern arises regarding the depletion of fossil fuels forcing us to find an alternative. Epoxidized product from vegetable oil via epoxidation process are one of the alternatives nowadays. Type of catalyst are one of the important parameters to be identify. Epoxidation of neem oil are set up where 100g of neem oil, 1:1 ratio of formic acid and 4:1 ratio of hydrogen peroxide towards neem oil are used, while the temperature to be fix at 700C and stir at 300 RPM for the whole process. Only catalyst is change for both experiment, which are amberlite 120 IR and zeolite ZSM-5 1g each. Results for both show promising relative conversion oxirane (RCO) where amberlite IR 120 at 49.5% meanwhile zeolite ZSM-5 at 47.34%. Epoxidation is successful because the FTIR spectra show formation of C-O which indicates epoxide bond at 1210cm-1 and OH group which are the by product also observed at 3450cm-1. Therefore, both catalysts can produce high RCO since the difference are only 2%. However, DHSA form from the degradation of oxirane ring can be focus on for the optimization of vegetable oils usage in the industry.